The war inside psychoanalysis, total war, and the making of the democratic self in postwar Britain - Shapira, Michal (Studies in the social and cultural history of modern warfare, 2013)
In recent years the field of modern history has been enriched by the exploration of two parallel histories. These are the social and cultural history of armed conflict, and the impact of military events on social and cultural history.